Quality of play, social acceptance and reciprocal friendship in preschool children - Coelho, Leandra Marques (2018)
Playing with peers is one of the most important contexts for the acquisition of social competencies in early childhood. This study examined the relation between children’s play behavior, social acceptance in the peer group, and number of reciprocal friendships. One hundred and twenty eight children, aged between three and five years, participated in the study. Social acceptance and number of reciprocal friendships were assessed using two sociometric measures: nomination and comparison among peers. Children’s behavior during play activities was assessed by a Portuguese version of the Penn Interactive Peer Play Scale. Global results showed positive and significant correlations between positive interaction and sociometric measures, indicating that children who manifest positive play behaviors are more accepted by peers and have more reciprocal friendships. On the other hand, play disruption and disconnection were negatively correlated with sociometric measures, indicating that children who show these types of play behaviors have lower social acceptance and fewer reciprocal friendships. Parsing the correlations by the three age groups, results show distinct patterns of associations between quality of play, social acceptance and friendship in function of age. Our results stress that already at an early age, behavior during play is related to friendship and social reputation.